Land Use Change Processes In the Slovenian Countryside In the Period 2000-2025 - Žiberna, Igor (Podeželje, 2026)
The chapter discusses the processes of land use change in rural areas in Slovenia in the period 2000-2025. In the introductory part, we typify rural areas with different criteria according to land use, namely at the level of mesoregions and at the level of settlements. In the following, we analyze the processes of land use change in rural areas. We pay special attention to arable areas. The directions of land use change and extensification coefficients in mesoregions and settlements in Slovenia are also analyzed. The results indicate processes of forking: cultivated areas, which in the past represented one of the important identities of the Slovenian countryside, are turning into meadows or overgrown land and into built-up areas. The gap between the declarative commitment to preserving cultivated areas and their actual abandonment is deepening.